Phonology and Online Media Used in Enhancing Listening Skill - Dwi Astuti Wahyu Nurhayati (Indonesian Journal of EFL and Linguistics, 2020)
This study examines how phonology and online media used to enhance students’ listening skill. The data were collected for 5 months starting from April to August 2020 in Islamic State Institute of Tulungagung (IAIN Tulungagung). The data were collected through questionnaire and interview. It involves college students who study and major English and have the relevant information about the research theme. It consist of 196 students of 3rd semester in IAIN Tulungagung. The finding reveals that there are some perspectives of students about the use of phonology and online media to enhance listening skill such as: the importance of online learning English media, online learning English media towards students’ attitudes in learning, the effect of online learning English media towards inferential listening, and media enhancing inferential listening skill. It was also gained students’ responses towards phonology used to enhance listening skill.